How can the transition from office to telework be managed? The impact of tasks and workplace suitability on collaboration and work performance - Müller, Tobias; Schuberth, Florian; Bergsiek, Micha; Henseler, Jörg (Frontiers in Psychology, 2022)
COVID-19 made evident the need for workplace digital transformation due to a rapid transition from office to remote work. Therefore, employers must make telework suitable for office workers who suddenly became permanent teleworkers. By using partial least squares path modeling, this article suggests the defining of telework tasks suitability and of telework workplace suitability by performing an empirical study with 691 employees who had experienced a rapid transition from office work to remote work during the pandemic. Both telework tasks suitability and telework workplace suitability are found to have a positive relationship with collaboration and work performance. Employers should therefore especially focus on communication technology when expecting employees work from home to improve work performance and enable collaboration to prevent them from feeling isolated. This study is the first to define telework tasks suitability and workplace suitability for enabling collaboration and improving work performance of teleworkers after an enforced transition from office working to teleworking.